(untitled) (Fiep Bulletin - online, 2011)
Data from the literature tend to reveal a great relationship between the development of mental functions and performance in several sports. For referees, there is a constant demand for professionals who make decisions quickly and efficiently. Self-efficacy and metacognition become central to these efforts, already covering the cognitive processes of higher order. Therefore, the development of new methods and tools of analysis appears to facilitate the search and drive new lines of work. In the literature, we observed that the growing interest in the phenomenon of self-efficacy metacognitive contrasts with the difficulty of measuring it, and that the search for an instrument to fill this methodological gap is needed. This initial analysis thus resulted in a version called Questionnaire Self-Efficacy for referees Metacognitive in collectives sports (QAEMAr). Looking to the reproducibility of this instrument in relation to content validity, it passed the examination of three experts. Finally, in a pilot study, this version was applied to referees (n = 50) of both sexes, the collective modes, at the University Brasillian - JUB ’S 2009. The difficulties reported by participants led to the development of a second version of the original questionnaire. Reproducibility was ensured by the high percentage of registered agreements, most of the above limits of 80%.